Evolution of the groundwater geochemistry in sulphide-rich mine tailings remediated by applying soil cover, Kristineberg, northern Sweden - Öhlander, Björn; Correge, O. (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2002)
Godkänd; 2002; 20120912 (ysko)